2014
DOI: 10.1371/journal.pone.0083256
|View full text |Cite|
|
Sign up to set email alerts
|

High Intensity Interval Training in a Real World Setting: A Randomized Controlled Feasibility Study in Overweight Inactive Adults, Measuring Change in Maximal Oxygen Uptake

Abstract: BackgroundIn research clinic settings, overweight adults undertaking HIIT (high intensity interval training) improve their fitness as effectively as those undertaking conventional walking programs but can do so within a shorter time spent exercising. We undertook a randomized controlled feasibility (pilot) study aimed at extending HIIT into a real world setting by recruiting overweight/obese, inactive adults into a group based activity program, held in a community park.MethodsParticipants were allocated into o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(122 citation statements)
references
References 32 publications
5
109
1
7
Order By: Relevance
“…Sete estudos avaliaram secundariamente [31][32][33][34][35][36][37] e cinco estudos tiveram controle alimentar 26,29,30,33,37 .…”
Section: Características Dos Estudos E Participantesunclassified
See 3 more Smart Citations
“…Sete estudos avaliaram secundariamente [31][32][33][34][35][36][37] e cinco estudos tiveram controle alimentar 26,29,30,33,37 .…”
Section: Características Dos Estudos E Participantesunclassified
“…As durações das sessões tiveram média de 35,7 ± 13,3 min e 44,7 ± 9,7 min para os grupos HIIT e CONT respectivamente. 34 . Nos estudos incluídos, treze estudos utilizaram recuperação ativa e apenas um estudo utilizou recuperação passiva.…”
Section: Duraçãounclassified
See 2 more Smart Citations
“…Aamot et al (2013) found that participants in Norway performing HIIT at home in their own chosen modality, whether it be cross-country skiing, cycling or cross-training, still met their target HR using a HR monitor. (317) Furthermore, a study by Lunt et al (2014) used the 4x4 protocol in outdoor group sessions. (318) Even though the authors found improvements in VO 2 peak to be slightly lower than previously observed in other studies, this study recognized the feasibility of HIIT in a real world setting.…”
Section: Section 2; Chapter 8 the Feasibility Of Hiit Vs Mictmentioning
confidence: 99%